2012
DOI: 10.1111/j.1365-2745.2012.01996.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial contiguity and continuity of canopy gaps in mixed wood boreal forests: persistence, expansion, shrinkage and displacement

Abstract: Summary 1. Variation in forest gap size and duration are a result of spatial contiguity and continuity of gap infilling and tree mortality over time, which influences both species recruitment and successional pathways. 2. As many gaps in boreal forests are small, their size and duration will affect the conditions influencing species recruitment. We investigate the spatial dynamics of these gaps (i.e. those which are persistent, ephemeral, expanding, displaced or disappearing) and tested whether gap spatio‐temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 57 publications
(67 reference statements)
2
23
0
Order By: Relevance
“…Gap size and distribution pattern were mapped from satellite imagery by Garbarino et al [23] and Hobi et al [24]. Vepakomma [25,26] used Light Detection and Ranging (LiDAR) to assess spatial contiguity and continuity of canopy gaps over time in mixed wood boreal forests. Rugani et al [27] based a similar research question using visual stereo interpretation of scanned color-infrared (CIR) aerial photographs.…”
Section: Introductionmentioning
confidence: 99%
“…Gap size and distribution pattern were mapped from satellite imagery by Garbarino et al [23] and Hobi et al [24]. Vepakomma [25,26] used Light Detection and Ranging (LiDAR) to assess spatial contiguity and continuity of canopy gaps over time in mixed wood boreal forests. Rugani et al [27] based a similar research question using visual stereo interpretation of scanned color-infrared (CIR) aerial photographs.…”
Section: Introductionmentioning
confidence: 99%
“…Gap dynamics in a landscape level have been detected widely recent years with the help of remote sensing technology (Andersen et al 2014). For example, Vepakomma et al (2012) characterized the gap dynamics over a 9-year period in a natural old-growth boreal forest based on Lidar monitoring, and found that gaps changed in various ways. However, these large-scale studies may not be suitable for acquiring detailed closure information which is closely related to species regeneration (Getzin et al 2014).…”
mentioning
confidence: 99%
“…Large gaps and gap centres are often colonized by light-demanding pioneer species1213, while small gaps are occupied more by shade-tolerant ones14. Small openings are also more frequently filled by clonal growth, whereas successful establishment via seed germination prevails in larger gaps15.…”
mentioning
confidence: 99%